The unfolding treatment landscape for men with castration-resistant prostate cancer. (November 2011) - Kim, Jenny J; Keizman, Daniel; Denmeade, Samuel R; Antonarakis, Emmanuel S
Castration-resistant prostate cancer is a disease that is fatal in virtually all patients. Docetaxel chemotherapy became the standard front-line agent based on the results of the TAX327 trial in 2004, with a survival advantage of 3 months achieved over mitoxantrone. Over the past few years, an improved understanding of the molecular biology of castration-resistance has resulted in expansion of the treatment armamentarium for advanced prostate cancer with the emergence of novel: androgen receptor-directed therapies, cytotoxic chemotherapies, as well as immunotherapies. Four different agents have very recently gained approval by the US FDA for the treatment of castration-resistant prostate cancer and this review will summarize the development, mechanism of action and safety and efficacy of these agents as demonstrated in preclinical, as well as clinical studies.